Colicin E2 Production and Release by Escherichia coli K12 and Other Enterobacteriaceae - PUGSLEY, ANTHONY P; GOLDZAHL, NICOLAS; BARKER, RUTH M (Journal of general microbiology, 1985)
1 Unité de Génétique Moléculaire, Institut Pasteur, 25 Rue du Dr Roux, Paris 75724, France 2 Microbiology Department, University of Dundee Medical School, Ninewells Hospital, Dundee DD1 9SY, UK ABSTRACT Summary: Previous work has shown that Escherichia coli K12 ColE2 + cells undergo a form of partial lysis and exhibit increases in lysophosphatidylethanolamine (lysoPE) and free fatty acid content due to activation of phospholipase A when induced to produce and release colicin E2. The increase in lysoPE content was assumed to be essential for efficient colicin release. These same characteristics are also presented by some natural ColE2 + isolates, and by other representatives of the Enterobacteriaceae after transformation with derivatives of a ColE2 plasmid. However, Salmonella typhimurium strains carrying ColE2 plasmids released colicin without partial lysis and without increasing their lysoPE content. A previously undetected minor phospholipid, which appeared in these and other strains only when they were induced to produce colicin, may be an important factor in colicin release. In ColE2 + E. coli K12, production of this new lipid was dependent on phospholipase A activation following expression of the ColE2 lysis gene. Some other ColE2 + strains did not respond to induction of colicin production in the same way as ColE2 + E. coli K12. These strains were less sensitive to inducer (mitomycin C) or unable to produce increased amounts of colicin in response to induction, or unable to degrade colicin once it was released. In general, the results suggest that colicin release occurs by the same or similar processes in the various strains tested, and support the continued use of E. coli K12 as the model strain for studying the mechanisms of colicin release.